Synthesis and DNA Binding Studies of a Tetraazamacrocyclotetradecane Co(II) Complex - Bi, Jian-Hong; Cao, Yuan-Ying; Cui, Man (Asian Journal of Chemistry, 2010)
A tetraazamacrocyclotetradecane cobalt(II) complex, CoL·(ClO4)2 (L = 5,5,7,12,12,14- hexamethyl-1,4,8,11-tetraazamacrocyclotetradecane) was synthesized and characterized by IR spectra and elemental analysis. The interaction of the CoL·(ClO4)2 with DNA were studied by cyclic voltammetry. In the presence of DNA, the reduction peak of CoL·(ClO4)2 shifted to more positive values and the peak current decreased significantly. The experimental results indicate that the complex could interact with DNA by intercalation binding.